First, let's solve what's inside the parentheses:
2 1/4 + 3 2/3
To add these mixed numbers, we need to convert them to improper fractions:
2 1/4 = 9/4
3 2/3 = 11/3
Now we can add them:
9/4 + 11/3
To add fractions, we need a common denominator, which in this case is 12.
Converting both fractions to have a denominator of 12:
(9/4) * (3/3) = 27/12
(11/3) * (4/4) = 44/12
Now we can add them:
27/12 + 44/12 = 71/12
This is the result inside the parentheses. Now let's solve the entire expression:
6 11/12 - (71/12)
To subtract fractions, we need a common denominator, which is already 12.
So we can now subtract:
6 - 71/12
To subtract mixed numbers, we need to combine the integer and the fraction parts:
6 = 72/12
Now we can subtract:
72/12 - 71/12 = 1/12
Therefore, the final result is 1/12.
Solve 6 11/12-(2 1/4+3 2/3) do it in parentheses first. show all your steps
1 answer